Some Issues Concerning the Institute of Exemption from CriminalLiability Due to the Expiration of the Limitation Period - Simonyan, Tigran (Bulletin of Yerevan University C: Jurisprudence, 2025)
The institution of exemption from criminal liability due to the expiration of the statute of limitations has been repeatedly discussed in various theoretical sources and commentaries. However, regarding many related issues, there is no unified approach in both legal theory and judicial practice.When examining the viewpoint that "due to the long time elapsed after the commission of a crime, the investigation becomes significantly more difficult, evidence loses its validity, and information in the memory of witnesses and victims becomes distorted or forgotten," it should be noted that with the advancement of modern information technologies—including artificial intelligence, video recording tools, new systems, and mechanisms for detecting and preserving evidence—this approach cannot withstand any criticism. Evidence of a crime can now be preserved for a very long time, which facilitates the effective conduct of legal proceedings.In cases involving the same crime, one individual may face long-term imprisonment, compensate for damages, and undergo numerous rehabilitation programs, while another may simply "do nothing" for a certain period and avoid criminal liability altogether.It has been noted that some manifestations of this institution are nothing more than instances of "prosecutorial justice," under which it is necessary to implement corresponding legislative amendments requiring that any decision to exempt a person from criminal liability must be made (approved) by a court.The author concluded that the institution of exemption from criminal liability due to the expiration of the statute of limitations is outdated. As criminal legislation evolves and improves, the possibility of exempting individuals from liability on these grounds should be eliminated.Additionally, it was pointed out that particularly problematic is Part 7 of Article 83, which states that "in this case, the statute of limitations resumes from the moment the person is detained or voluntarily surrenders." This legal provision is unjustified and, in the author's opinion, should be removed from the text of the said article. Since the statute of limitations ceases to run once a decision to initiate criminal prosecution is made, the provision on its resumption is untenable.
Keywords: release from criminal liability; statute of limitations; statute of limitations passing; statute of limitations expiration; interruption of statute of limitations; suspension of statute of limitations; resumption of loss of evidence; inexpediency of criminal liability